Profitability of cassava-maize production under different fallow systems and land-use intensities in the derived savanna of southwest Nigeria - Chianu, Jonas N.; Akintola, J.O.; Kormawa, P.M. (Cambridge University Press, 2002)
Population pressure has diminished the role of the traditional bush fallow system in restoring the fertility of depleted soils following several years of cultivation in the derived savanna of southwest Nigeria. The search for alternative fallow systems led to the development of alley cropping using Leucaena leucocephala and cover cropping using Pueraria phaseoloides. These soil-conserving systems also embody the principles of sustainability by ensuring stable crop yields in spite of an increase in land-use intensity. Simulating smallholder farm conditions and based on a split-plot experiment with the three fallow systems as the main plots and four different land-use intensities (LUI) as the subplots, simple direct observation and record keeping were used to collect data on labour use in all farm operations including fuelwood cutting and stacking in alley cropping systems with fallow phases. Data collection covered a period of four years (1993±96), corresponding to one out of the three phases (or complete cycles) of the trial. Partial budget analysis was used to estimate proÆtability of cassava (Manihot utilissima)±maize (Zea mays) under each LUI. Results based on crop production indicate that each of the cassava-maize enterprises was proÆtable but the level of proÆt varied from 10 819 to 50 289 Naira ha7 1. Production under cover cropping has a net beneÆt advantage of 4±25% (over that under bush fallow) and 25±60% (over alley cropping). ProÆtability increased as the LUI decreased, depicting the overall importance of fallow periods on soil fertility restoration. Results based on crop production plus fuelwood operations indicate that production with cover cropping has a net beneÆt advantage over that of both bush fallow and alley cropping under both zero-fallow and one-year fallow LUIs. However, results from two- and three-year fallows indicate that fuelwood yield generated sufÆcient revenue to put alley cropping at a net beneÆt advantage of 29±42% over bush fallow and 26±37% over cover cropping. From these results, cover cropping is recommended, especially to farmers in areas where, although land shortage is a problem, fuelwood and the other sources of domestic energy are still cheap and easily accessible. However, in areas with abundant land and where farmers can still wait for fallow periods of at least two years, alley cropping is recommended since, in addition to soil fertility improvement, substantial revenue is obtained. However, considerations of yield variability, labour scarcity, as well as risk-aversion behaviour among farmers may alter their technology choice.